The Special Aspects of Leasing as Long-Term Asset Financing Method in Hungary - Darabos, Éva; Rózsa, Attila (International Journal of Engineering and Management Sciences, 2017)
Leasing has become widespread in the world in the 1970s, while in Hungary the first leasing firms appeared in the 1990s. The authors in this article introduce the most prevailing and most often used forms of leasing and their main characteristics in Hungary. Based on the statistical data of the 2008-2015 period the authors analyse the performance of investments, the volume of trade in the total leasing market and the course of the amount of capital assets and new capital investments on the level of the national economy. The conclusion of the current article is that the changes of the investment’s performance in the national economy and the EU development funds influence greatly the course of the Hungarian leasing market.